Ù…Ø¯ÙˆÙ†Ø© Ø§Ù„ÙÙŠØ¯ÙŠÙˆ (Vlog) ÙƒØ¨Ø¯ÙŠÙ„ Ù„Ù„ÙˆØ³Ø§Ø¦Ø· Ø§Ù„ØØ¯ÙŠØ«Ø© ÙÙŠ ØªØ¹Ù„Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨Ù‚Ù„Ù…: Ù…ÙØªØ§Ø Ø§Ù„ØªÙˆØ¨Ø© : Ù…Ø¯ÙˆÙ†Ø© Ø§Ù„ÙÙŠØ¯ÙŠÙˆ (Vlog) ÙƒØ¨Ø¯ÙŠÙ„ Ù„Ù„ÙˆØ³Ø§Ø¦Ø· Ø§Ù„ØØ¯ÙŠØ«Ø© ÙÙŠ ØªØ¹Ù„Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨Ù‚Ù„Ù…: Ù…ÙØªØ§Ø Ø§Ù„ØªÙˆØ¨Ø© - Miftachul Taubah (Lughatu Ad-Dhat, 2022)
Generation Z or the pro gadget generation is a generation that is friendly or familiar with technology. The problem that often occurs during learning is learning that tends to pay attention to lecturers and prefers to use their gadgets in low learning motivation. Vlog is a medium that can be used for Project Based Learning-based learning. Through project assignments, students can understand the material being studied effectively. The project task is in the form of making a Vlog, suitable for use in learning Arabic. This is because Vlogs tend to tell stories, the result of which is video content (audio visual). Through the use of Vlogs, students can be more creative and see in learning Arabic, especially developing their maharah kalam. This is because in the process of making vlogs, students learn to speak Arabic, explain or describe what content they are making.